CONTRIBUTION TO THE SPRING VEGETATION OF THE JULIAN ALPS: THE ASSOCIATION CRATONEURETUM FALCATI GAMS 1927 - Surina, Boštjan (Hacquetia, 2015)
Phytosociological characteristics of stands with predominating Cratoneron commutatum var. falcatum (=Palustriella commutata var. falcata) in the Krn Mts. and Mt. Mangart (the Julian Alps) are presented. After the comparison with similar stands from the Karavanke Mts. they are ranged into the association Cratoneuretum falcati (Cratoneurion commutati, Montio-Cardaminetea).